The impact of HIRAID on emergency nurses' self-efficacy, anxiety and perceived control: A simulated study. (March 2016) - Munroe, Belinda; Buckley, Thomas; Curtis, Kate; Murphy, Margaret; Strachan, Luke; Hardy, Jennifer; Fethney, Judith
Highlights: Low anxiety and high self-efficacy enhances clinical reasoning and performance. HIRAID provides emergency nurses with a structured approach to patient assessment. HIRAID reduces emergency nurses' anxiety when conducting patient assessments. HIRAID increases emergency nurses' self-efficacy in performing patient assessments. Abstract: Introduction: Emergency nurses must perform accurate and complete comprehensive patient assessments to establish patient treatment needs and expedite care. Aim: To evaluate the impact of a structured approach to emergency nursing assessment following triage, on novice emergency nurses' anxiety, self-efficacy and perceptions of control. Methods: Thirty eight early career emergency nurses from five Australian hospitals performed an initial patient assessment in an immersive clinical simulated scenario, before and after undertaking training in HIRAID, an evidence-informed patient assessment framework for emergency nurses. Immediately following each scenario the nurses completed a questionnaire scoring anxiety, self-efficacy and perceptions of control levels. Paired sample t-tests and effect sizes were calculated. Results: Participant anxiety levels were lower after HIRAID training compared to before undertaking the training (Mean (SD) = 53.26 (10.76) vs 47.46 (9.96), P  = 0.002). Self-efficacy levels in assessment performance increased (189.32 (66.48) vs 214.06 (51.35), P  = 0.001). There was no change in perceptions of control (31.24 (7.38) vs 30.98 (8.38), P  = 0.829). Discussion: High levels of anxiety and low levels of self-efficacy are known to be negatively correlated with clinical reasoning skills and performance. Conclusion: The effect of HIRAID training on reducing anxiety and increasing self-efficacy has the potential to improve emergency nurses' assessment performance and the quality and safety of patient care.